1 & 2 Timothy and Titus - Ngewa, Samuel (Michigan Zondervan, 2009)
Includes bibliographical references
Includes bibl. refs.
Keywords: Bible. N.T. Timothy -- Commentaries; Bible. N. T. Titus -- Commentaries